Full-scale laboratory testing of a buried pipeline in sand subjected to cyclic axial displacements - Sheil, B; Martin, C; Byrne, B; Plant, M; Williams, K; Coyne, D (Thomas Telford (ICE Publishing), 2018)
This paper describes a full-scale laboratory study of the axial sliding behaviour of a trenched pipeline surrounded by sand backfill. Cyclic axial displacements are applied to a heavy pipe buried in a narrow trench (less than three pipe diameters wide), using various backfill cover depths and two different soils: dry Hostun sand and a damp silty sand. A novel testing tank is employed, with compressible foam seals to allow the pipe to settle as it moves axially, and a pressure bag system to simulate backfill depths exceeding the height of the tank. The test pipe is instrumented to measure (a) the axial soil resistance developed on an isolated central section of pipe (thus avoiding tank boundary effects), and (b) the normal and shear contact stresses at a number of points around the pipe circumference. The results indicate that both the axial resistance and the normal stress distribution around the pipe can undergo considerable changes when a pipeline experiences cyclic axial displacements. An extreme case identified here is the potential for a compacted damp sand backfill to ‘arch’ completely over the pipe as a result of differential settlement, leading to unexpectedly low axial resistance. To address some limitations of the design method currently used in industry, a new approach for estimating axial resistance is suggested and applied to the present test data.